(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2013)
This paper seeks to examine one aspect of the dosage of punishment in the Criminal Action 470/MG, known as “Mensalão” process. The criminal process in question has been widely commented and analyzed by its importance in the political history of our country as the scope of innovations positioning of the Supreme Court in criminal matters. The study specifically addresses to the initial regimen of imprisonment, as well as the parameters used for fixation.